LATIHAN CLOSED KINETIC CHAIN LEBIH EFEKTIF DARIPADA OPEN KINETIC CHAIN UNTUK MENINGKATKAN KEMAMPUAN FUNGSIONAL PADA KONDISI OSTEOARTHRITIS LUTUT - Yana Yunita, Alfitri; -, Marliana; Andam Dewi, puti (LPPM Universitas Awal Bros, 2024)
Osteoarthritis is a disease caused by degenerative factors of the knee that suffered damage to joint cartilage so people with osteoarthritis usually complain of pain, stiffness and limitation of function. Knee osteoarthritis has the most common cause to limited motion and body function. This aimes of study to determine closed kinetic chain exercise was better than open kinetic chain to increase functional capability of knee osteoarthritis. The design of this research was experimental pre-test and post-test with control group design, which the population was taken by purposively sampling. Division of the sample into two groups, group one consisted of 10 people. The first group was given Closed Kinetic Chain exercise and group two was given Open Kinetic Chain exercise. The frequency of exercise are 3 times a week for 4 weeks. Increase in ability functional measured by Western Ontario and McMaster Universities Ostearthritis Index (WOMAC). Analysis of significance with Paired ttest (paired) showed that in each group resulted in an increase in functional ability after treatment of knee osteoarthritis is significantly different p<0,05. While a difference test in both groups after treatment using analysis test of Independent t test (unpaired) showed that the value of p=0,019. So thah there was an increase functional capabilities of knee osteoarthritis after treatment p<0,05. In conclution the treatment Closed Kinetic Chain proved improvement the functional capabilities of knee osteoarthritis than the Open Kinetic Chain.